SAY 'FAREWELL' TO CORRUPTION: A WAY FORWARD TO COMBAT MALARIA (CASE STUDY CAMEROON) - TATA, Joseph Ngoe (Graduate School of International Studies Ajou University, 2010)
ABSTRACT Malaria is a disease transmitted by a specific kind of mosquito known as anopheles. However, there are four types of human malaria but the deadly variant which is responsible for the wide spread of malaria cases in Africa is caused by the pathogen called plasmodium falciparum. Even though the disease is treatable and preventable it has remained a killer disease claiming the lives mostly of children under age five and pregnant women. According to data published from World Health Organization (WHO) and the US Centers for Disease Control and Prevention (CDC) in 2005, showed that about 18% of children under age five die of malaria and every 30 seconds a child die of malaria. In economic terms, malaria has been estimated to lead to a drop in 1/3% of economic growth rates in countries affected by the disease. Knowing well that the life cycle of the parasite is greatly favored by high temperatures, countries therefore in the tropical regions like Cameroon will record a high incidence of malaria proliferation. As a result therefore, much has been put in by international organizations such as the United Nations through the UNDP, the millennium development goals (MDG6) which is aimed at fighting HIV/AIDS, malaria, tuberculosis and other related diseases to be achieved by 2015. African leaders through the Abuja declaration are also putting more efforts by working as a team to fight the disease and also agreeing that the 25th of April each year will be celebrated as ？Africa malaria day？ in order to raise awareness to the public about the deadly disease. The governments of Cameroon and local NGOs have made much effort to fight the disease by raising public awareness through the media, the provision of subsidized drugs and the free distribution of mosquito nets. All these efforts have helped reduce the rate of the spread of disease but not very significantly as malaria still remain a threat to human health. The government as well as other perspectives holds the view that malaria is much as a result of poverty and so much of their efforts in combating the disease is tilted towards addressing poverty first and then malaria. However, this work is focused on the view that widespread corruption is the result of the increase spread of malaria and also an impediment to the measures put forward to combat the disease. It also posits a network of cooperation between the government, NGOs and the private sector as the possible solution for the fight against the deadly disease based on a bottom-up ( grass root ) approach, while undermining conflicting interest which create more tension and lead to a general failure of much useful efforts.
학위논문(석사)--아주대학교 국제대학원--NGO학과,2010. 8